Multiple Myeloma: EHA-ESMO Clinical Practice Guidelines for Diagnosis, Treatment and Follow-up. Issue 2 (3rd February 2021) - Dimopoulos, Meletios A.; Moreau, Philippe; Terpos, Evangelos; Mateos, María-Victoria; Zweegman, Sonja; Cook, Gordon; Delforge, Michel; Hájek, Roman; Schjesvold, Fredrik; Cavo, Michele; Goldschmidt, Hartmut; Facon, Thierry; et al.
Abstract : Supplemental Digital Content is available in the text.